The 1.24–1.21 ga licheng large igneous province in the North China craton: Implications for paleogeographic reconstruction - Wang, Chong; Peng, P.; Li, Zheng-Xiang; Pisarevsky, Sergei; Denyszyn, S.; Liu, Yebo; Gamal El Dien, Hamed; Su, X. (AMER GEOPHYSICAL UNION, 2020)
Detailed geochronological, geochemical, and paleomagnetic studies of mafic dyke swarms, often associated with mantle plumes, can provide unique constraints on paleogeographic reconstructions. Mafic dykes with baddeleyite U–Pb ages of 1,233 ± 27 Ma (SIMS), 1,206.7 ± 1.7 Ma (TIMS), 1,214.0 ± 4.9 Ma (TIMS), and 1,236.3 ± 5.4 Ma (TIMS) have been identified in the eastern North China Craton. Geochemical data indicate subalkaline to alkaline basalt compositions with OIB‐like trace element signatures and an intraplate tectonic setting. In addition to these geochemical signatures, the radiating geometry of these dykes also suggests a 1.24–1.21 Ga large igneous province caused by a mantle plume event. A new ~1.24 Ga paleomagnetic pole at 2.0°N, 165.1°E, A95 = 11.0°, N = 9 and an ~1.21 Ga VGP at −23.0°N, 92.5°E, dp/dm = 4.7°/7.8° have been obtained from these dykes, with the 1.24 Ga pole supported by positive baked contact test. Our paleomagnetic analyses suggest that the North China Craton and the proto‐Australian continent could have been separated by 1.24–1.21 Ga from an established Nuna connection at ca. 1.32 Ga. By comparison with Laurentia paleopoles, we present the paleogeography of dispersing North China, proto‐Australian, and Laurentia cratons in the late Mesoproterozoic during the breakup of the supercontinent Nuna.